Identification and distribution of pyrene, methylpyrenes and their isomers in rock extracts and crude oils. (June 2015) - Fang, Ronghui; Li, Meijun; Wang, T.-G.; Zhang, Liwen; Shi, Shengbao
Highlights: We identify C1 –C2 alkylated pyrenes and their isomers in oils and sediment extracts. We study the distribution of pyrenes in oils and extracts with different origins. Two oil families are distinguished in the Tarim Basin based on pyrenes. The 2-/1-methylpyrene ratio can be used as maturity indicator. Abstract: Pyrene (Py), its alkylated homologues, fluoranthene (Fla), benzo[ a ]fluorene (B a F) and benzo[ b ]fluorene (B b F) have been unequivocally identified in crude oils and sedimentary rocks by co-injection with authentic standards and comparison of retention indices with those reported in the literature. The distribution patterns of pyrene, its C1 –C2 alkyl derivatives and their isomers were then investigated in oils and sedimentary rocks with Early Paleozoic and Cenozoic origins. The oil groups of Ordovician–Cambrian reservoirs in the cratonic region of the Tarim Basin (NW China) are distinguished on the basis of the distribution patterns of pyrene, fluoranthene and their methylated homologues. The majority of the oil accumulations are characterized by low concentrations of fluoranthene and methylfluoranthenes relative to pyrene and methylpyrenes, respectively. In contrast, oils from wells TD2, TZ26, TZ162 and TZ451 have relatively higher concentrations of fluoranthene and methylfluoranthenes, indicating different origins. The distribution patterns of methylpyrenes in Cenozoic lacustrine shales from the Liaohe Basin (East China) show effects of maturity, where the 2-/1-MPy and MPYR (2-MPy/(2-MPy + 1-MPy)) ratios display a regular increase with increasing maturity. This study shows that pyrene, its alkylated homologues and their isomers are useful molecular markers in petroleum geochemistry and that the 2-/1-MPy and MPYR ratios are potential maturity indicators.